Impact of COVID-19 therapy on hyperglycemia. (May 2022) - Parise, Rachel; Deruiter, Jack; Ren, Jun; Govindarajulu, Manoj; Ramesh, Sindhu; Nadar, Rishi M; Moore, Timothy; Dhanasekaran, Muralikrishnan
The goal of this study was to analyze the effect of COVID-19 drugs and biologicals on hyperglycemia. A literature search with key terms, such as "COVID-19 drugs and hyperglycemia" and "COVID-19 vaccines and hyperglycemia, " was conducted using PubMed through September 2021. The CDC data were referenced for current COVID-19 profile and statistics. The NIH COVID-19 guidelines were referenced for updated treatment recommendations. Micromedex and UpToDate were used for drug and disease information. Current results suggested that corticosteroids (dexamethasone), remdesivir and antivirals (lopinavir and ritonavir) all have the potential to significantly raise blood glucose levels putting patients at elevated risk for severe complications. In contrary, hydroxychloroquine is associated with hypoglycemia, and tocilizumab decreases inflammation which is associated with improving glucose levels. Other anti-cytokine bioactive molecules are correlated with lower blood glucose in patients with and without diabetes mellitus. Ivermectin, used for mild COVID-19 disease, possesses the potential for lowering blood glucose. Covishield, Pfizer-BioNTech, and Moderna have all been associated with hyperglycemia after the first dose. Individualized /personalized patient care is required for diabetic mellitus patients with COVID-19 infection. Improper drug therapy aggravates hyperglycemic conditions and other comorbid conditions, leading to increased morbidity and mortality.